Public support for empowering police during the COVID-19 crisis: evidence from London - Yesberg, Julia A. (Policing and society, 2024)
In the face of the COVID-19 pandemic, police services around the world were granted unprecedented new powers to enforce social distancing restrictions. In this paper, we present data from a rolling representative sample survey of Londoners (n = 3,201) fielded during the height of the first wave of the pandemic (April to June 2020). We examine the scale of public support for giving police additional powers to enforce the regulations, whether support for different powers ebbed and flowed over time, and which factors predicted support for police powers. First, we use interrupted time-series analysis to model change over time. Second, we pool the data to test the predictors of support for police powers. Aside from one lockdown-specific temporal factor (the easing of restrictions), we find that even in the midst of a pandemic, legitimacy, procedural justice and affective evaluations of pandemic powers are the most important factors explaining variation in public support for police empowerment.